Hadith #6444 - Sahih Muslim - Abu Burzah al-Aslami (Sahih Muslim)
Go ahead (but that dromedary did not move). She (that slave-girl), out of anger, said: O Allah, let that (dromedary) be damned. Thereupon Allah’s Apostle (ﷺ) said: Let the dromedary on which the curse has been invoked not proceed with us.
Grade: Sahih

Hadith #948 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I would see the Messenger of Allah (ﷺ) praying two rak’ahs of Fajr and making them so brief that I said: ‘Did he recite the Umm Al-Kitab in them?'”
Grade:

Hadith #4071 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tauba al-'Anbari al-Basri توبة العنبري البصري (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever changes his religion, kill him.'”
Grade:

Hadith #4072 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever changes his religion, kill him.'”
Grade:

Hadith #4073 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Abu Da'ud أبو داود السجستاني الأزدي; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Sa'id bin Fyrwz Abu al-Bakhtari al-Tai'i سعيد بن فيروز أبو البختري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever changes his religion, kill him.'”
Grade:

Hadith #4074 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sa'id bin Fyrwz Abu al-Bakhtari al-Tai'i سعيد بن فيروز أبو البختري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Yahya bin Hmad bin Aby يحيى بن حماد بن أبي زياد الشيباني (Sunan al-Nasa'i)
Ibn ‘Abbas said: “The Messenger of Allah said: ‘Whoever changes his religion, kill him.'”
Grade:

Hadith #4075 - Sunan al-Nasa'i - Abdullah ibn Ja'far; Abu Burzah al-Aslami; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Mua'wiya bin Salah bin al-Wazir معاوية بن صالح بن الوزير; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Zayd ibn Harithah (Sunan al-Nasa'i)
‘Ali came to some people of Az-Zutt, who worshipped idols, and burned them. Ibn ‘Abbas said: “But the Messenger of Allah said: ‘Whoever changes his religion, kill him.'”
Grade:

Hadith #4076 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Abu Da'ud أبو داود السجستاني الأزدي; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“That the Prophet to you.’ Abu Musa gave him a cushion to sit down, then a man was brought who had been a Jew, then he became a Muslim, then he reverted to Kufr. Mu’adh said: ‘I will not sit down until he is killed; this is the decree of Allah and His Messenger,’ (saying it) three times. When he was killed, he sat down.”
Grade:

Hadith #4077 - Sunan al-Nasa'i - Abu Burzah al-Aslami; Abu Da'ud أبو داود السجستاني الأزدي; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Hameed bin Hilal حميد بن هلال; Yazid bin Zari' يزيد بن زريع; Yonus bin 'Ubaid bin Dinar يونس بن عبيد بن دينار العبدي (Sunan al-Nasa'i)
“On the day of the Conquest of Makkah, the Messenger of Allah . He (‘Uthman) said: ‘O Messenger of Allah! Accept the allegiance of ‘Abdullah.’ He raised his head and looked at him three times, refusing his allegiance each time, then he accepted his allegiance after three times. Then he turned to his Companions and said: ‘Was there not any sensible man among you who would get up when he saw me refusing to give him my hand and kill him?’ They said: ‘We did not know, O Messenger of
Grade:

Hadith #3185 - Sunan Abi Dawud - Abu Burzah al-Aslami; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Ja'far bin Iyas; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
A man fell ill and a cry was raised (for his death). So his neighbour came to the Messenger of Allah (ﷺ) and said to him: He has died. He asked: Who told you? He said: I have seen him. The Messenger of Allah (ﷺ) said: He has not died. He then returned. A cry was again raised (for his death). He came to the Messenger of Allah (ﷺ) and said: He has died. The Prophet (ﷺ) said: He has not died. He then returned. A cry was again raised over him. His wife said: Go to the Messenger of Allah (ﷺ
Grade: Sahih

Hadith #4847 - Sunan Abi Dawud - Abu Burzah al-Aslami; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
She saw the Prophet (ﷺ) sitting with his arms round his legs. She said: When I saw the Messenger of Allah (ﷺ) in such humble condition in the sitting position (according to Musa’s version), I trembled with fear.
Grade: Hasan

Hadith #4857 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Burzah al-Aslami; Abu Hashim al-Rmany أبو هاشم الرماني; Hjaj bin Dinar حجاج بن دينار; Muhammad bin Hatm bin Yonus محمد بن حاتم بن يونس; Uthman bin Muhammad (Sunan Abi Dawud)
There are some expressions which a man utters three times when he gets up from an assembly he will be forgiven for what happened in the assembly; and no one utters them in an assembly held for a noble cause or for remembrance of Allah but that is stamped with them just as a document is stamped with a signet-ring. These expressions are: Glory be to Thee, O Allah, and I begin with praise of Thee, there is no god but thou; I ask Thy pardon, and return to Thee in repentance.
Grade: Sahih

Hadith #4878 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Burzah al-Aslami; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: When I was taken up to heaven I passed by people who had nails of copper and were scratching their faces and their breasts. I said: Who are these people, Gabriel? He replied: They are those who were given to back biting and who aspersed people’s honour. Abu Dawud said: Yahya b. ‘Uthman has also transmitted it from Baqiyyah, there is no mention of Anas in it.
Grade: Sahih

Hadith #168 - Jami' al-Tirmidhi - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Abu Burzah al-Aslami; Ahmad bin Hanbal أحمد بن حنبل; Ahmed bin Manay' أحمد بن منيع; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال (Jami' al-Tirmidhi)
“The Prophet would dislike to sleep before Isha and to talk after it.”
Grade:

Hadith #2531 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi عبد الله بن عبد الرحمن الدارمي; Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Burzah al-Aslami; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Jami' al-Tirmidhi)
“Indeed there are a hundred levels in Paradise, if all of the People of Paradise were to be gathered in one of them, it would have sufficed them.”
Grade:

Hadith #867 - Sunan Ibn Majah - Aabad bin al-Wam bin عباد بن العوام; Abu Burzah al-Aslami; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Ibn Majah)
It was narrated from ‘Amr bin Shu’aib, from his father, from his grandfather, that the Messenger of Allah (ﷺ) forbade sitting in circles in the mosque on Fridays before the prayer.
Grade:

Hadith #1552 - Sunan Ibn Majah - Abu Burzah al-Aslami; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Ali bin al-Hazur/ 'Ali bin Abi Fatima علي بن الحزور/علي بن أبي فاطمة (Sunan Ibn Majah)
Mu’adh bin Jabal said: “The Messenger of Allah (ﷺ) sent me to Yemen and commanded me to take one-tenth of that which was irrigated by deep roots, and to take one half of one-tenth of that which was irrigated by means of buckets.”
Grade:

Hadith #2266 - Sunan Ibn Majah - Abu Burzah al-Aslami; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Ahmed bin al-Miqdam أحمد بن المقدام; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق (Sunan Ibn Majah)
“O Umair, I have set you free in a good way. I heard the Messenger of Allah (ﷺ) say: ‘Any man who frees a slave and does not say anything about his (the slave’s) wealth, it belongs to him (the slave).’ So tell me, how much wealth do you have?” Another chain reports a similar hadith.
Grade: